A Flagella Hook Coding Gene flgE Positively Affects Biofilm Formation and Cereulide Production in Emetic Bacillus cereus - Li, Yangfu; Chen, Nuo; Wu, Qingping; Liang, Xinmin; Yuan, Xiaoming; Zhu, Zhenjun; Zheng, Yin; Yu, Shubo; Chen, Moutong; Zhang, Jumei; Wang, Juan; Ding, Yu (Frontiers in Microbiology, 2022)
Bacillus cereus, an important foodborne pathogen, poses a risk to food safety and quality. Robust biofilm formation ability is one of the key properties that is responsible for the food contamination and food poisoning caused by B. cereus, especially the emetic strains. To investigate the mechanism of biofilm formation in emetic B. cereus strains, we screened for the mutants that fail to form biofilm by using random mutagenesis towards B. cereus 892-1, an emetic strain with strong biofilm formation ability. When knocking out flgE, a flagellar hook encoding gene, the mutant showed disappearance of flagellar structure and loss of motility. Further analysis revealed that both pellicle and ring presented defects in the null mutant compared with the wild type and complementary strains. Compared with the flagellar paralytic strains ΔmotA and ΔmotB, the inhibition of biofilm formation by ΔflgE is not only caused by the inhibition of motility. Interestingly, ΔflgE also decreased the synthesis of cereulide. To our knowledge, this is the first report showing that a flagellar component can both regulate the biofilm formation and cereulide production in emetic B. cereus, which can be used as the target to control the biohazard of emetic B. cereus.